Catch basin larvicide treatments impact adult mosquito West Nile virus vector species in metropolitan Milwaukee, WI, U.S.A. - Haley E. Johnson; Justin E. Harbison; Jessica L. Hite; Bradley J. Tucker; J. Mitchell Kirsch; Susan Paskewitz; Lyric C. Bartholomay (PLoS ONE, 2026)
Roadside stormwater catch basins are frequently treated with larvicides in metropolitan areas because they are ideal larval growth sites for West Nile virus (WNV) vector species Culex pipiens Linnaeus and Cx. restuans (Theobald) . Despite the wide-spread implementation of catch basin treatments in integrated vector management programs, there is little entomological evidence to suggest catch basin larvicide treatments reduce adult mosquito abundance and thereby impact WNV risk. We evaluated the impact of treating catch basins at three of four sites (700–1000 basins each) with a formulation of Lysinibacillus sphaericus using a stepped-wedge cluster trial approach in metropolitan areas in Wisconsin, U.S.A in 2019. Treatment effects were measured by evaluating immature stage mosquito abundance in catch basins and general additive models (GAM) to analyze changes of the integrated adult female Culex spp. abundance and population stability sampled from host-seeking and gravid mosquito traps. We observed catch basin treatments to effectively suppress immature stages in catch basins (94% reduction of pupae). The GAM found catch basin treatment duration to significantly reduce the integrated abundance of gravid Culex spp. mosquitoes, with a total mean percent reduction of 37% at treated sites. Treatment duration was also observed to impact the stability of the gravid Culex spp. integrated abundance, with differences between untreated and treated sites, and among sites that differed in treatment duration. These results support the treatment of catch basins with biorational larvicides as a mosquito management tool for WNV vector species in similar metropolitan habitats provided adequate suppression of immature stage mosquitoes.